The Development of EliteVet: Veterinary Clinic Management System - Abd Latiff, Nur Muhammad Nashriq; Ab. Aziz, Ruhaya (Applied Information Technology And Computer Science, 2025)
In veterinary clinics, efficient management of customer’s information and appointment booking are critical for delivering high-quality care. However, many clinics still rely on traditional paper-based systems, leading to challenges such as incomplete or inaccurate customer records and inefficient appointment booking processes. As a result, EliteVet was created for Elite Veterinary Clinic and Surgery Tampin. This is related to various problems that customers confront, such as the difficulty of filling out information on printed paper cards and the difficulty of making appointments for pets. This project presents a solution using a prototyping model and object-oriented approach in developing and designing the proposed system. Hypertext Pre-Processor (PHP) language was selected for the development code, Visual Studio Code as a code editor, and MySQL to access the database. In addition, this system provides customers, pets, doctor's information, appointments, treatment, and pet hotel bookings, online payments, and report management. Overall, the proposed system will demonstrate significant improvements in handling customer information and appointment booking, ultimately enhancing the service quality and operational efficiency of Elite Veterinary & Surgery Clinic.